Quality of Higher Education in Conditions of Distance and Blended Learning: Experience of Surveying Students of the Specialty «Pediatrics» on the Study of Biological Chemistry - Yanitska, Lesya; Stechenko, Olena; Obernikhina, Nataliya (Educological discourse, 2025)
With the beginning of the COVID-19 pandemic, most institutions of higher education faced new challenges related to the need to fully or partially implement distance learning. In Ukraine, with the beginning of a large-scale war, the situation with the educational process became extremely complicated. Therefore, the issue of maintaining the quality of education, under the conditions of complex and unpredictable changes, acquired special importance. In particular, the distance and mixed education of students of the specialty 228 “Pediatrics” in biological chemistry became the model thanks to which the main approaches and algorithms for improving the training process of future doctors using powerful process management mechanisms and the internal system of ensuring the quality of education were worked out. The educational environment created before the beginning of the academic year with the involvement of the university’s distance learning platform, scientific and pedagogical staff of the department with their personal skills, abilities and methodological techniques, and the student contingent of the 2nd year of the specialty «Pediatrics» became the elements of the educational process that during the academic year changed, improved, developed and studied. After the first semester of studying the discipline, an anonymous survey was conducted in order to find out the level of satisfaction of higher education applicants, followed by a debriefing of the results. The improvement of the educational environment, the development of teachers’ skills and their rotation, carried out based on the results of the debriefing, became key steps to increase the level of satisfaction of the 2nd-year higher education students when they mastered biological chemistry as the main component of the «Pediatrics» educational program. The effectiveness of the introduced changes was studied using repeated anonymous questionnaires of students after they had completed the academic discipline. Comparing the results of the first and second surveys showed that satisfaction with the quality of lectures increased by 1.4 %, while the level of dissatisfaction decreased by 1.3 %. Also, the level of satisfaction with the quality of conducting practical classes in biological chemistry increased by 2.1 %, while the level of dissatisfaction decreased by 2.2 %.